Au cœur des ténèbres, une œuvre ambiguë, et discussion par Boniface Mongo-Mboussa - Boniface Mongo-Mboussa; Blaise Ndala (Continents manuscrits)
Blaise Ndala revisits the discomfort he felt when reading 'Heart of Darkness' at the end of his studies. This discomfort persists: why did Conrad choose the Congo Basin to set the scene of his novella? Why does, under his pen, the black man become a half mute half savage puppet?